Mechanized harvesting of first crop of coffee - Santinato, Felipe [UNESP] (2015)
Mechanized harvesting of coffee in the crop's first harvest has restrictions on its use. There are assumptions that this type of harvesting can increase damage to plants and increase the amount of coffee falling on the ground. In this context, present study aimed to evaluate the harvest efficiency and damage to the coffee plants by the harvesters in first harvest of crop. Two situations of crop were compared: mature and immature crops. In both, the harvesting operations were conducted with two harvesters, A and B (adapted automotive coffee harvester and common combine harvester) operating in two intensities (I - operating speed of 1,200 m h(-1) and the sticks vibration of 600 rpm and II - operating speed of 1,000 m h(-1) and 850 rpm). The treatments were studied in factorial 2 x 2 + 1, outlined in blocks, with five repetitions. The harvest efficiency, amount of fallen and remaining coffee grains, damage to plants and leaves of crop after the execution of the harvest were evaluated. It was found that the mechanical harvesting of first crop of coffee plantations should only be made using adapted harvesters. Mechanized coffee harvesting, promotes minor damage to the plants than manual harvest.